Investigating how blood cadmium levels influence cardiovascular health scores across sexes and dose responses - Feng Chen; Feng Chen; Hao Lin; Yuansi Zhang; Yu Zhang; Shaohe Chen (Frontiers Media S.A., 2024)
BackgroundThe association between exposure to cadmium (Cd) and cardiovascular health (CVH) has received considerable scientific interest. However, findings thus far have been inconclusive, particularly regarding sex-specific effects and dose-response relationships. The aim of our study was to investigate the relationships of blood Cd levels with the overall and component CVH scores.MethodsWe used data from the 2011-2018 NHANES to assess CVH using indicators such as BMI, blood pressure, lipid profiles, glucose levels, diet, physical activity, nicotine use, and sleep quality, each rated on a 0-100 scale. The overall CVH score was calculated as the average of these indicators. We employed both multiple linear and restricted cubic spline analyses to examine the relationship between blood Cd levels and CVH scores, including nonlinear patterns and subgroup-specific effects.ResultsOur analysis revealed that higher blood Cd levels were associated with lower overall CVH, nicotine exposure, sleep, and diet scores, with nonlinear decreases observed in overall CVH and nicotine exposure scores at specific thresholds (−1.447 and −1.752 log μg/dL, respectively). Notably, sex differences were evident; females experienced more adverse effects of Cd on CVH and lipid scores, while in males, Cd exposure was positively correlated with BMI, a link not observed in females.ConclusionOur study highlights the complex interplay between blood Cd levels and various aspects of CVH, revealing significant dose-response relationships and sex disparities. These findings enhance our understanding of the biobehavioral mechanisms linking Cd exposure to cardiovascular risk.